Agenda governamental no Brasil: análise da atenção presidencial na nova república (1985-2014) - Sudano, Andréia di Camilla Ghirghi Pires (2018)
This thesis investigated the dynamics of attention given by different Brazilian presidents to policies based on the following question: how was presidential attention directed to prioritize certain issues in its legislative decisional agenda between 1985 and 2014? The general objective was to understand, from the comparative evaluation of its composition and changes, the patterns of prioritization of presidential attention in the perspective of its legislative decisional agendas. The analysis of the data was based on the absolute and relative frequency of the policies expressed in the presidential legislative proposals, codified according to the typology of the Comparative Agenda Project (CAP). A descriptive analysis was performed, based on the absolute and relative size of the samples (number of propositions by type, president, government and political party of the president), as well as measures of central tendency and dispersion of the relative frequencies of policies (average, standard error, asymmetry, kurtosis and standard deviation); and (2) statistical analyzes of the relative frequencies of attention to policies, using uni- and multivariate data models (Pearson's correlation, analysis of variance- ANOVA, principal component analysis -PCA- and partial least squares-discriminant analysis -PLS-DA), with the aid of statistical software, to understand differences and to establish comparisons between groups (presidents, governments and political parties). In the results, the product from the presidential priorities was discussed by: (A) presentation of the content emphasized by them in their legislative decision-making agendas (composition and attributes); (B) evaluation of changes (increase, decrease or stability) in presidential attention to policies; (C) comparison (similarities and differences) between the agendas by president, government and political party. As attributes, we observed activist agendas (high capacity), broad (high diversity) and with little variation of volatility. As an exception, one has the agenda of President Dilma Housseff, restrained (low capacity) in comparison with the others. In addition, there was a great convergence of presidential attention to the same issues, which corroborates the indication of institutional and cognitive restrictions imposed on legislative decisional agendas. Presidents of different parties at different times consolidated a similar attention to the set of policies that were presented. However, it was possible to diagnose differences between presidents and changes over the period that expressed the preferences and contingencies that were submitted to each one. The comparative analysis made it possible to discuss the policies with greater emphasis in each group, suggesting the influences that affected the selection and prioritization of policies by the presidents expressed in their legislative decisional agendas.